Voltaire and Crébillon père - David, P; LeClerc, P (Voltaire Foundation, 2017)
Preface Introduction Chapter I. The Contestants Chapter II. Casus belli Chapter III. First skirmishes Chapter IV. Attack and counterattack Chapter V. The Elusive victory Conclusion List of works consulted